Modulating EGFR-MTORC1-autophagy as a potential therapy for persistent fetal vasculature (PFV) disease. Issue 6 (2nd June 2020) - Yazdankhah, Meysam; Shang, Peng; Ghosh, Sayan; Bhutto, Imran A.; Stepicheva, Nadezda; Grebe, Rhonda; Hose, Stacey; Weiss, Joseph; Luo, Tianqi; Mishra, Subrata; Riazuddin, S. Amer; Ghosh, Arkasubhra; et al.
ABSTRACT: Persistent fetal vasculature (PFV) is a human disease that results from failure of the fetal vasculature to regress normally. The regulatory mechanisms responsible for fetal vascular regression remain obscure, as does the underlying cause of regression failure. However, there are a few animal models that mimic the clinical manifestations of human PFV, which can be used to study different aspects of the disease. One such model is the Nuc1 rat model that arose from a spontaneous mutation in the Cryba1 (crystallin, beta 1) gene and exhibits complete failure of the hyaloid vasculature to regress. Our studies with the Nuc1 rat indicate that macroautophagy/autophagy, a process in eukaryotic cells for degrading dysfunctional components to ensure cellular homeostasis, is severely impaired in Nuc1 ocular astrocytes. Further, we show that CRYBA1 interacts with EGFR (epidermal growth factor receptor) and that loss of this interaction in Nuc1 astrocytes increases EGFR levels. Moreover, our data also show a reduction in EGFR degradation in Nuc1 astrocytes compared to control cells that leads to over-activation of the mechanistic target of rapamycin kinase complex 1 (MTORC1) pathway. The impaired EGFR-MTORC1-autophagy signaling in Nuc1 astrocytes triggers abnormal proliferation and migration. The abnormally migrating astrocytes ensheath the hyaloid artery, contributing to the pathogenesis of PFV in Nuc1, by adversely affecting the vascular remodeling processes essential to regression of the fetal vasculature. Herein, we demonstrate in vivo that gefitinib (EGFR inhibitor) can rescue the PFV phenotype in Nuc1 and may serve as a novel therapy for PFV disease by modulating the EGFR-MTORC1-autophagy pathway. Abbreviations: ACTB: actin, beta; CCND3: cyclin 3; CDK6: cyclin-dependent kinase 6; CHQ: chloroquine; COL4A1: collagen, type IV, alpha 1; CRYBA1: crystallin, beta A1; DAPI: 4ʹ6-diamino-2-phenylindole; EGFR: epidermal growth factor receptor; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFAP: glial fibrillary growth factor; KDR: kinase insert domain protein receptor; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MKI67: antigen identified by monoclonal antibody Ki 67; MTORC1: mechanistic target of rapamycin kinase complex 1; PARP: poly (ADP-ribose) polymerase family; PCNA: proliferating cell nuclear antigen; PFV: persistent fetal vasculature; PHPV: persistent hyperplastic primary vitreous; RPE: retinal pigmented epithelium; RPS6: ribosomal protein S6; RPS6KB1: ribosomal protein S6 kinase, polypeptide 1; SQSTM1/p62: sequestome 1; TUBB: tubulin, beta; VCL: vinculin; VEGFA: vascular endothelial growth factor A; WT: wild type.